Strategi Pemerintah Republik Indonesia dalam Penanganan Masalah Pelintas Batas Indonesia-Timor Leste - Remigius Seran (Jurnal Hubungan Internasional, 2018)
ABSTRACTThe urgency to set up the Border Between Indonesia and Timor-Leste and the border crossers is based on much more complex historical reasons than the arrangement of Indonesia's borders with other countries. Border governance policies between Indonesia and Timor-Leste are characterized by: border governance policies indicate a desire to adopt an integrated approach, governance practices tend to be fragmented where two very dominant approaches are the security approach and the socio-economic welfare approach. A border governance policy that ignores cultural identity variables leads to a reverse response, namely the use of cultural identity to challenge the country's dominant conception and policy in border governance. The phenomenon of "rat road" and other cross-border interaction networks called illegal by the state can be read as a form of local community resistance to the claim of state sovereignty over the border. In an integrated border governance policy, a cultural approach should be one of the main components that characterize other approaches. Jailly puts the four dimensions of the policy parallel, the cultural approach in border governance policy to the principles that fuel security policy, local politics and economic policy in border governance. The practical consequence of this study is the policy that border governance must move beyond the dominance of the economic security approach to an integrated approach. This study proposes the concept of trans-border social and cultural space as an important element in integrated border governance.Key Words: Border governance, Indonesia – Timor-Leste, Cultural crosser borders.